Pure and mixed forest plantations with native species of the dry tropics of Costa Rica: a comparison of growth and productivity - Piotto, D.; Viquez, E.; Montagnini, F.; Kanninen, M. (2004)
In Costa Rica, most reforestation trials with native species were established in the tropical humid region. In the dry tropics, research on the performance of native species in forest plantations is incipient and trials comparing pure and mixed designs are limited. This paper presents the results of two experimental plantations with native trees in pure and mixed plots in the dry tropics of Costa Rica. The growth and productivity of 13 native species in pure and mixed plantations was compared with Tectona grandis (L.f.) Lam, an exotic species broadly used in the region. In a plantation of relatively slower growing species, measurements taken at 68 months of age resulted in Samanea saman (Jacq.) Merril. and Dalbergia retusa Hemsl. demonstrating the best growth, followed by Astronium graveolens Jacq. and Swietenia macrophylla King. Measurements in a plantations of relatively faster growing species, at 68 months of age, showed that growth of Schizolobium parahyba (Vell.) Blake was greatest in the pure and mixed plots, followed by Terminalia oblonga (Ruiz & Pav.) Steud., Anarcadium excelsum (Bert. & Balb. ex Kunth) Skeels and Pseudosamanea guachapele (Kunth) Harms. The native species grew better in the mixed plots. The pure plots of T. grandis (L.f.) Lam. were the most productive, compared to all species and the mixture of species. Plantations of T. grandis (L.f.) Lam. seem to be well adapted to the region and are certainly a commercially interesting alternative. Nevertheless, mixed plantations with native species would contribute more to sustainable management, because while single-species plantations do not provide a great range of goods and services when compared to the natural forest, mixed plantations are likely to increase this range of benefits.